2011
DOI: 10.1111/j.1365-2966.2011.19217.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy and Mass Assembly (GAMA): the GAMA galaxy group catalogue (G3Cv1)

Abstract: Using the complete Galaxy and Mass Assembly I (GAMA‐I) survey covering ∼142 deg2 to rAB= 19.4, of which ∼47 deg2 is to rAB= 19.8, we create the GAMA‐I galaxy group catalogue (G3Cv1), generated using a friends‐of‐friends (FoF) based grouping algorithm. Our algorithm has been tested extensively on one family of mock GAMA lightcones, constructed from Λ cold dark matter N‐body simulations populated with semi‐analytic galaxies. Recovered group properties are robust to the effects of interlopers and are median unbia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
483
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 334 publications
(499 citation statements)
references
References 41 publications
16
483
0
Order By: Relevance
“…The spectroscopic group-satellite catalogue used in this work has a high, but not 100 per cent, purity. For groups with N FoF ≥ 5 the purity approaches 90 per cent; groups with fewer members have significantly lower purity (Robotham et al 2011). Li et al (2013) have shown that a contamination fraction of 10 per cent in the satellite sample would lead to a +15 per cent bias in the inferred satellite masses, well within the reported uncertainties (which amount to up to a factor 2).…”
Section: Sensitivity To Contamination In the Group Cataloguesupporting
confidence: 62%
See 4 more Smart Citations
“…The spectroscopic group-satellite catalogue used in this work has a high, but not 100 per cent, purity. For groups with N FoF ≥ 5 the purity approaches 90 per cent; groups with fewer members have significantly lower purity (Robotham et al 2011). Li et al (2013) have shown that a contamination fraction of 10 per cent in the satellite sample would lead to a +15 per cent bias in the inferred satellite masses, well within the reported uncertainties (which amount to up to a factor 2).…”
Section: Sensitivity To Contamination In the Group Cataloguesupporting
confidence: 62%
“…1 the stacked ESD of all 9683 satellites residing in groups with N FoF ≥ 5. We also show the ESD around all galaxies in the GAMA catalogue, which is dominated by (central) field galaxies (Robotham et al 2011). The lensing signal around the two samples is qualitatively different.…”
Section: The Satellite Lensing Signalmentioning
confidence: 99%
See 3 more Smart Citations